2020
DOI: 10.3390/ijms21134596
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and General Glucocorticoid Physiology in Skeletal Muscles Affected by Duchenne Muscular Dystrophy: Exploration of Steroid-Sparing Agents

Abstract: In Duchenne muscular dystrophy (DMD), the activation of proinflammatory and metabolic cellular pathways in skeletal muscle cells is an inherent characteristic. Synthetic glucocorticoid intake counteracts the majority of these mechanisms. However, glucocorticoids induce burdensome secondary effects, including hypertension, arrhythmias, hyperglycemia, osteoporosis, weight gain, growth delay, skin thinning, cushingoid appearance, and tissue-specific glucocorticoid resistance. Hence, lowering the glucocort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 159 publications
(256 reference statements)
1
23
0
Order By: Relevance
“…The molecular mechanism(s) responsible for prednisone’s clinical efficacy in DMD is still under investigation, but at least part of the mechanism is likely due to it its anti-inflammatory effects. The binding of prednisone (and other glucocorticoids) to the glucocorticoid receptor triggers the inhibition of the transcription factor nuclear factor kappa-light-chain-enhancer of activated B cells, which is responsible for causing inflammation [reviewed by Herbelet et al ( 42 )]. Although C. elegans lack an inflammatory system and satellite cells ( 16 ), prednisone is still able to improve DMD worm health.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular mechanism(s) responsible for prednisone’s clinical efficacy in DMD is still under investigation, but at least part of the mechanism is likely due to it its anti-inflammatory effects. The binding of prednisone (and other glucocorticoids) to the glucocorticoid receptor triggers the inhibition of the transcription factor nuclear factor kappa-light-chain-enhancer of activated B cells, which is responsible for causing inflammation [reviewed by Herbelet et al ( 42 )]. Although C. elegans lack an inflammatory system and satellite cells ( 16 ), prednisone is still able to improve DMD worm health.…”
Section: Resultsmentioning
confidence: 99%
“…The paper reviews patterns of muscle, respiratory and systemic involvement in infantile facioscapulohumeral muscular dystrophy and biomarkers of the disease, as well as therapeutic approaches and standard care for individuals with infantile facioscapulohumeral muscular dystrophy. The seventh paper, titled “Anti-Inflammatory and General Glucocorticoid Physiology in Skeletal Muscles Affected by Duchenne Muscular Dystrophy: Exploration of Steroid-Sparing Agents”, by [ 7 ] provides an overall presentation of the drugs that have been shown to stabilize the activation of proinflammatory and metabolic cellular pathways in skeletal muscle cells in Duchenne muscular dystrophy, as well as possible combinations of drugs with glucocorticoid therapy. The eighth paper, titled “Cognitive Deficits in Myopathies”, by [ 8 ] classifies myopathies according to their clinical characteristics and reviews concomitant cognitive deficits.…”
Section: Papersmentioning
confidence: 99%
“…Corticosteroids are also commonly used and show limited success in Duchenne muscular dystrophy (DMD, OMIM 310200), a very severe and the most common form of degenerative muscular pathology. Long-term clinical trials showed that prednisolone/prednisone or deflazacort corticosteroids reduce chronic muscle inflammation, stabilise muscle function, prolong ambulation and improve respiratory function and patients’ survival [ 7 , 8 , 9 ]. However, several side effects are associated with the prolonged usage of these immuno-modulators, the most severe being a drastic inhibition of the immune system’s functionality, occasionally leading to life-threatening opportunistic infections.…”
Section: Marketed Pharmacological Treatmentsmentioning
confidence: 99%